Effects of HIV-related worries on fertility motivation moderated by living children among couples living with HIV: A dyadic analysis - Guo, Yingwu; Du, Yingrong; Liu, Jun; Bai, Jingsong; Gao, Jianpeng; Wu, Lei; Yang, Yongrui; Wang, Weibo; Chen, Jie; Xu, Zhaoyuan; Yan, Junfang; Lu, Nihong; et al. (Frontiers in Psychology, 2022)
IIntroduction: HIV-related worries are a major barrier to achieving fertility goals for couples living with HIV (CLWH). We examined the moderating role of living children in the association between HIV-related worries and fertility motivation in CLWH including happiness, well-being, identity, and continuity. Methods: The data of 322 reproductive-aged CLWH were collected for this cross-sectional study from a referral antiretroviral therapy clinic in Kunming, China between October and December 2020. Intra- and interpersonal mechanisms of association between HIV-related worries and fertility motivation moderated by the number of living children in husband-wife dyads were analyzed by the actor-partner interdependence moderation model. Results: The high-level HIV-related worries of the wives and husbands were associated with the spouses’ fertility motivation. Having at least one child helped to ameliorate the negative association between one’s own HIV-related worries and fertility motivation. However, there was no evidence of such moderation in the spouse. Conclusion: Whether the CLWH has at least one living child should be taken into account in counseling. Childless families should be counseled on HIV-related worries as those worries have a greater negative effect on fertility motivation than couples who have a child.